2017
DOI: 10.1186/s12884-017-1631-y
|View full text |Cite
|
Sign up to set email alerts
|

Facility-imposed barriers to early utilization of focused antenatal care services in Mangochi District, Malawi – a mixed methods assessment

Abstract: BackgroundFocused Antenatal Care (FANC) is advocated by the World Health Organization (WHO) as a key service approach to improving the health of pregnant women. Four targeted visits to antenatal clinics are recommended starting in the first trimester. First trimester attendance for FANC in Mangochi District, Malawi was low at 8%. FANC has mainly been promoted through health facility based communication activities with less emphasis on activities at community level. We developed and tested a community focused h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 14 publications
6
26
0
Order By: Relevance
“…A similar finding has been reported in recent studies in Tanzania and Malawi [31,32]. These studies indicated that pregnant women who did not bring their partners were denied ANC services.…”
Section: Discussionsupporting
confidence: 90%
“…A similar finding has been reported in recent studies in Tanzania and Malawi [31,32]. These studies indicated that pregnant women who did not bring their partners were denied ANC services.…”
Section: Discussionsupporting
confidence: 90%
“…These findings have been supported by a previous study (Mamba et al. ) which revealed that women are not permitted to visit their doctors without their husband being present. These beliefs and practices should be viewed as resulting from the general conservative sociocultural and religious background of people in Bangladesh and Malawi.…”
Section: Discussionsupporting
confidence: 82%
“…In general, the mothers felt it was important to attend, in particular, to have a physical examination, and see that all was well with the growing foetus. A recent study in Mangochi District found institutional barriers to early ANC attendance that need to be addressed in order to improve coverage (Mamba, Muula, and Stones 2017).…”
Section: Process Indicatorsmentioning
confidence: 99%